Replication of epidemiological associations of carpal tunnel syndrome in a UK population-based cohort of over 400,000 people - Wiberg, A; Smillie, RW; Dupré, S; Schmid, AB; Bennett, DL; Furniss, D (Elsevier, 2021)
Introduction Several phenotypic factors are associated in the literature with an increased risk of carpal tunnel syndrome (CTS). Along with female sex and older age, certain systemic diseases show an association with CTS, with varying degrees of evidence. Methods This study was performed using the UK Biobank resource – a cohort study of over 500,000 participants who have allowed linkage of phenotypic data with their medical records. We calculated the prevalence of CTS and a sex-specific prevalence ratio, and compared the body-mass index (BMI) between cases and controls. We performed a series of nested case-control studies to compute odds ratios for the association between CTS and three systemic diseases. Results There were 12,312 CTS cases within the curated UK Biobank dataset of 401,656 (3.1% prevalence), and the female:male ratio was 1.95:1. CTS cases had, on average, a BMI > 2.0 kg/m2 greater than controls. Odds ratios for the association with CTS for three systemic diseases were 2.31 (95% CI 2.17–2.46) for diabetes, 2.70 (95% CI 2.44–2.99) for rheumatoid arthritis, and 1.47 (95% CI 1.38–1.57) for hypothyroidism. Adjusted for BMI, these odds ratios fell to 1.75 (95% CI 1.65–1.86), 2.43 (95% CI 2.20–2.69), and 1.35 (95% CI 1.26–1.43), respectively. Discussion We harnessed the size and power of UK Biobank to provide robust replication of evidence for the associations between CTS and female sex, raised BMI, and three systemic diseases, which are only mediated in part by raised BMI.